Guinea : Second Review of the Arrangement under the Three-Year Extended Credit Facility, financing Assurances Review, and Request for a Waiver of Nonobservance of Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Guinea. (IMF Staff Country Reports; Country Report, 2019)
Guinea's strong growth momentum continues. Real growth reached about 10 percent in 2017 and is expected at about 6 percent in 2018 and 2019. However, the social context remains fragile. Risks of political and social instability are heightened by upcoming legislative elections in March 2019 and presidential elections in 2020.